2021
DOI: 10.1007/s11056-021-09888-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in early seasonal growth efficiency and productivity of eucalyptus genotypes

Abstract: Understanding the changes in early growth efficiency (GE, growth/leaf area) may improve forest production through the selection of appropriate genotypes at early stages. We investigated different early growth responses of genotypes of Eucalyptus globulus (7), E. nitens (3), and E. nitens × E globulus (E. gloni) (7) in south-central Chile. To evaluate seasonal growth, plants of each genotype were established in a completely randomized block design in coarse sandy soil (i.e., low water holding capacity), with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The growth response to water stress over time and its genetic variation in Eucalytpus genotypes has been analyzed using the water stress integral concept [79,80] (Figure 3). Low productivity varieties showing higher levels of accumulated stress response over time may represent the responses of sensitive species to seasonal water stress (Figure 3a) [81]. For example, Waghorn et al [82], researching juvenile Pinus radiata, concluded that lateseason drought (higher WSI levels) is more detrimental to diameter growth and biomass accumulation compared to early-season drought (Figure 3b).…”
Section: Implication Of Response To Stress For Species or Genotype Se...mentioning
confidence: 99%
See 2 more Smart Citations
“…The growth response to water stress over time and its genetic variation in Eucalytpus genotypes has been analyzed using the water stress integral concept [79,80] (Figure 3). Low productivity varieties showing higher levels of accumulated stress response over time may represent the responses of sensitive species to seasonal water stress (Figure 3a) [81]. For example, Waghorn et al [82], researching juvenile Pinus radiata, concluded that lateseason drought (higher WSI levels) is more detrimental to diameter growth and biomass accumulation compared to early-season drought (Figure 3b).…”
Section: Implication Of Response To Stress For Species or Genotype Se...mentioning
confidence: 99%
“…time may represent the responses of sensitive species to seasonal water stress (Figure 3a) [81]. For example, Waghorn et al [82], researching juvenile Pinus radiata, concluded that late-season drought (higher WSI levels) is more detrimental to diameter growth and biomass accumulation compared to early-season drought (Figure 3b).…”
Section: Implication Of Response To Stress For Species or Genotype Se...mentioning
confidence: 99%
See 1 more Smart Citation